2019
DOI: 10.1111/pde.14067
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to treatment with thalidomide in an adolescent with generalized discoid lupus erythematosus

Abstract: Discoid lupus erythematosus (DLE) is the most common variant of cutaneous chronic lupus erythematosus (CLE).Sun protection, topical corticosteroids, and antimalarials constitute the first-line options for treatment. In refractory cases, alternative antimalarials, methotrexate, retinoids, and thalidomide have been utilized. We present a case of an adolescent patient with generalized DLE responding rapidly to thalidomide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In case reports, treatment with HCQ as monotherapy or in combination with other treatments resulted in improvement in alopecia secondary to variants of CLE, including DLE, LEP, and tumid LE. 12,20,28,30,44,[57][58][59] It is important to note that HCQ above a dose regimen of 5 mg/kg is associated with significant ocular toxicity and should be avoided. 60…”
Section: Corticosteroids and Antimalarialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case reports, treatment with HCQ as monotherapy or in combination with other treatments resulted in improvement in alopecia secondary to variants of CLE, including DLE, LEP, and tumid LE. 12,20,28,30,44,[57][58][59] It is important to note that HCQ above a dose regimen of 5 mg/kg is associated with significant ocular toxicity and should be avoided. 60…”
Section: Corticosteroids and Antimalarialsmentioning
confidence: 99%
“…50,82,83 Thalidomide has also been reported to significantly improve alopecia associated with DLE in a pediatric patient. 59 However, its use is limited by severe side effects, including teratogenicity, peripheral neuropathy, and thrombosis, as well as frequent relapses after withdrawal of therapy. 42,50,[82][83][84] In several non-comparative trials and observational studies, lenalidomide proved efficacious in treating refractory CLE, without inducing or worsening peripheral neuropathy.…”
Section: Dapsonementioning
confidence: 99%
“…However, relapses after drug withdrawal were developed by nearly all patients, even if less severe (65). Subsequent case series or small sized studies reported similar results with doses of mainly 50-100 mg daily (63,(65)(66)(67)(68)(69).…”
Section: Thalidomidementioning
confidence: 68%
“…Thalidomide is an immunomodulator treatment used in multiple inflammatory disorders. 6 Its use in several photodermatosis, particularly lupus erythematous 7 and actinic prurigo, 8…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide is an immunomodulator treatment used in multiple inflammatory disorders 6 . Its use in several photodermatosis, particularly lupus erythematous 7 and actinic prurigo, 8 had shown good results. Its mode of action in the case of CAD is poorly understood.…”
Section: Discussionmentioning
confidence: 99%